Effects of coal mining on groundwater in Mukah, Sarawak, Malaysia - Aruh @ Aro, Joseph Jubin (2013)
With the present trend of increasing crude oil price globally, coal will be an attractive alternative of energy resource for electricity power generation in Malaysia. The presence of major elements such as SiO2 Al2O3, Na2O, K2O, Fe2O3, MnO, MgO, P2O5 and SO3 and several trace elements such as (As), Cu and Pb in the coal bodies contaminate both groundwater and surface water. The hydrocarbon waste from workshops, leaching of heavy metals from coal preparation plants, coal stockpiles, overburden dumps and refuse emplacement within coal mining area elevated further the content of contaminants. Coal mine tailings such as aggravated mud and organics substances filling oxbows contain ferric sulphides (FeS2). The shallow and unconfined groundwater aquifers in the study area with water table ranging from 0.1m to 1.23m below vadose zone are exposed to the influx of these contaminants. The production of acid mine drainage which contains arsenic, iron compound, nitrate and carbonate compound will pose problem to the existing biodiversity and the surrounding environment, with no exemption to surface water and groundwater to the on going coal mining area of about 192 km2. The problem of acid drainage due to the presence of sulphur in coal bodies is a common in coal mining areas. Coal waste, which oxidized to acid residue, will eventually lead to surface water and groundwater problems. Visual features such as workshops, preparation plants, coal stockpiles, overburden dumps and refuse emplacement within vicinity of mining area can be a threat to the surrounding environment. This research investigate the effects of opencast coal mining on the groundwater quality and the surrounding watershed including seepage of mining contaminants, transportation mechanisms of pollutants and its pathway into groundwater aquifer. The geological, stratigraphy, bore holes logging and the water quality data are analyzed and explored to the objectives of the research. The geology of study area is simple. The Balingian Formation which is unconformable overderlain by Begrih Formation covers most of the study area. The southern part is underlain by younger Liang Formation hosted massive lignite bed. The Quaternary deposits, mudstone/shale, and sandstone with subordinate of mudstone, Begrih Conglomerate, and coal seam are common.The primary data of groundwater is obtained by laboratory analysis of groundwater samples from the wells. The sampling of groundwater is done by storing it in polyethylene bottle and treated with bactericide to prevent contamination of the water samples. The groundwater is analyzed for major and minor elements including Cl-, SO42- , HCO3, NO3-(anions), Ca+, Na+, K+, Mg2+(cations), Fe, As, Mn, Cu, Cyanide, Zn, and Pb (heavy metals). Other properties of groundwater analyzed are odour, pH, colour, turbidity, electrical conductivity (EC), total dissolved solids (TDS), hardness (CaCO3, DO, COD, and BOD) The physico-chemical data of groundwater properties, clay, and coal from the coal mining area in Mukah are explored and analyzed by using IBM Statistical Package for the Social Sciences (SPSS) version 20. The multivariate analysis of variance (MANOVA) and principal component analysis (PCA) are computed to investigate the important variables and the relationship among the variables. The Principle component analysis (PCA) explains the acidity and the presence of Fe, Mn, Ca, K, SO4, HCO3, CO3, Cl and total dissolved solids in groundwater samples and to extract the important major elements such as SiO2 , Al2O3, Na2O, K2O, TiO2, Fe2O3, MnO, MgO, CaO, P2O5 and SO3 in both coal ash and clay deposits. The values of Mn, Mg and Fe are higher and slightly more acidic than groundwater outside coal mining area. The production of acidic water is due to ferric sulphide produces sulphate and free sulphuric acid under aerobic condition in the presence of water. The statistical analysis reveal that coal and clay deposits contributed to the elevated values of metals elements and production of acid mine water. The principal components of clay are TiO2, Na2O, K2O, and MgO where as the principal component of coal ash are MgO, CaO, P2O5, SiO2, Al2O3, TiO2, Fe2O3, MnO and SO3. The groundwater affected by coal mining shows relatively low the concentrations of metals (Cu, Pb, Zn, Cd, and Al) except for Fe having value of 1.4 mg/l and slightly higher than Malaysian water quality standards. Mukah groundwater is classified into SO4 type, HCO3 type and no dorminant type (intermediate). The analysis lithologic data, wireline logging, resistivity imaging lines and from the Ground Penetrating Radar runs are used to interpret the hydrostratigrahic and the groundwater flow within the study area. The results of geological, geophysical, stratigraphic correlation facilitate in creating conceptual model for the intrusion of pollutant into groundwater aquifer. The elevation and groundwater heads data were computed in surfer programme to create the 3D image by gridding method using kriging point method. The modflow vistas and MapInfo programme are used to predict the general flow direction of groundwater within Mukah coal field. The locations of the drill holes and groundwater wells are plotted on the digitized map by using Arcgis software. The elevation and groundwater heads plots indicate that groundwater flows from northeast to southwest and from central part of the mining area the direction of flow is westerly. In the central part of the Coal mining area groundwater flows radially. The problems arise from many coal producing countries has given extra dimension in protecting groundwater from being contaminated by coal mining. The planting of trees or top soil cover plants, the construction of sediment trap or filter and settlement pond are recommended as the best practice in maintaining and protecting of the groundwater from being polluted.